Board of Directors, Audit Committee and Firms’ Performance - Awad, Ghina (2023)
This study explores the different attributes of audit committees and boards of directors' effect on firm performance. Mainly the board’s size and independence and the audit committee’s employment, size, independence, financial experience, and frequency of meetings. This paper also talks about resource dependency theory which considers that. Non-independent directors have a positive effect on firm performance. On the contrary, agency theory suggests that the more independent the board is, the better the performance. Many accounting scandals and worldwide failures in corporate governance have occurred in the past few decades, affecting stakeholders and taking a heavy toll on national and global economies. After many infamous corporates, the United States passed the Sarbanes-Oxley Act (SOX), which acted to heighten the responsibilities of the board of directors in corporations, promotes fairness to both shareholders and stakeholders alike by enforcing listed companies to employ independent, knowledgeable, and proactive audit committees and directors and ultimately set the utmost importance on the protection of investors and stakeholders. Taking a sample of 96 companies, the results show that a more extensive and independent board positively affects business results, and the same applies to the implementation of an audit committee. However, our results found no link between the different characteristics of audit committees with firm performance. The findings above give us insight into how companies’ governance operates.